Pendapatan Usaha Dalam Home Industry Kerupuk Sagu - Ibni Humam; Jalaluddin Wafi (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2023)
Most of the employees in this home industry are men who live around the home industry. With this business, it becomes a source of income or additional income for the surrounding community and becomes a new job opportunity for the community or teenagers who do not attend high school but have skill